Prevalence of Fordyce's Granules among Adult Dental PatientsAttending a Provincial Hospital in Janakpurdham, Nepal: ADescriptive Cross-Sectional Study - Chaudhary, Raju Kumar; Jha, Mina; Chaulagain, Rajib (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Fordyce’s granules are ectopic sebaceous glands that are usually localized in the oral mucosa. They appear in the oral cavity as an elevation and are detected in routine dental examination. There is a paucity of data related to Fordyce’s granules in the Nepalese population. This study aimed to study the prevalence of Fordyce’s granules in the oral cavity of adult dental patients attending a provincial hospital in Janakpurdham, Nepal.Methods: A descriptive cross-sectional study was conducted among 279 dental patients visiting the Provincial hospital, Janakpurdham, Nepal. Ethical approval to conduct the study was obtained from the Institutional Review Committee of Madhesh Institute of Health Sciences (MIHSIRC/082/083-22). The participants’ oral cavities were examined using a mouth mirror under adequate illumination. The findings were recorded in the proforma, which was later analyzed using descriptive statistical methods with Statistical Package for the Social Sciences version 16.Results: A total of 279 adults with a mean age of 36.14 ± 9.72 years participated in the study. Among the participants, 155 (55.56%) were male. The prevalence of Fordyce’s granules was 104 (37.28%). The highest prevalence of Fordyce’s granules was observed in the 20–29-year age group, 34 (32.70%). The majority of the Fordyce’s granules were observed in the retromolar area on the right side, 87 (16.89%), followed by the right buccal mucosa, 73 (14.17%). Conclusions: The findings confirm that Fordyce's granules are a common finding in this population, with a prevalence of 37.28%. They were most common in young adults and were primarily located in the retromolar area and the buccal mucosa.